Meaning and Interpretation - Hagberg, G. L. (Cornell University Press, 2022)
'What is the meaning of a word?' In this thought-provoking book, Hagberg demonstrates how this question—which initiated Wittgenstein's later work in the philosophy of language—is significant for our understanding not only of linguistic meaning but of the meaning of works of art and literature as well.